Hackers rule. (Economist, 1999)
On February 15, 1999, 100 protestors gathered next to Microsoft's Silicon Valley offices to demonstrate against the “Windows tax.” The protestors argued that computer users have to pay dues to Microsoft because nearly all personal computers come with Windows and that consumers using other operating systems, such as Linux, should get a refund. Linux is the most successful example of software developed by a loose fraternity of volunteers rather than by a company's in-house programmers. Such “open-source” software challenges the way the software industry, and Microsoft in particular, has always conducted its business. The writer discusses the success of Linux, the advantages of open-source software, how open-source software and programming was developed, the drawbacks to such development, and ways employed to tackle these problems.